Reliability improvement of power systems using shunt reactive compensation and distributed generation - Mohammad Mahmoud; Ayman Faza (Institute of Advanced Engineering and Science, 2023)
Due to the increased demand on electric power, power systems have become highly stressed. This has caused the frequent occurrence of cascading failures, where the failure of one line leads to a series of failures causing a system blackout. Adding high speed control of different electrical parameters of the power system can help improve the reliability of the power system and relieve some of that stress. In this research, the effects of adding static VAR compensators (SVCs) and distributed generation units has been studied from a reliability perspective. Since installing this equipment can be expensive, an algorithm has been developed to obtain the optimal bus location to install such devices, such that reliability is improved. Furthermore, Monte Carlo simulation is used to provide a measure for the improvement in system reliability in the presence of transmission line failures. Results show that injecting real and reactive power generally improves system reliability. However, increasing the amount of injection and increasing the number of buses injected to indefinitely does not necessarily enhance the reliability of the system any further. As such, caution must be exercised when deploying SVCs or distributed generation sources when the goal is to improve system reliability.